Employer characteristics and youth employment outcomes in the formal sector in South Africa: Assessment using administrative tax data - Stewart Ngandu; Carolyn Chisadza (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Through the use of administrative tax data, this study attempts to identify the characteristics of firms that employ relatively large numbers of young people. The policy objective of this exercise is to use these insights to inform policy and programming in the context of youth unemployment, particularly regarding where efforts to intensify youth absorption into employment should be focused to ensure maximum impact in addressing the problem of low youth employment in South Africa. Given the nature of this new data set, we adopt an explorative approach and make use of various econometric models to conduct the analysis within the limitations of the variables in different tax data sets. The novelty of this paper is that it uses unique administrative tax micro-data sets, which allows us to explore the relationship between firm characteristics and youth employment in South Africa with a significantly large sample size.
Keywords: C55; C80; D22; E24; 330; Administrative data; tax; firm level; firm behaviour; employment; unemployment